Studi eksperimen kinerja turbin vortex berbasis gravitasi dengan sudu backward dan forward - Pamuji, D.S.; Akbar, F.; Rohman, A.N.; Sugati, D. (Dinamika Teknik Mesin, 2021)
Nowadays, the use of hydro energy in Indonesia is still focused on large-scale hydropower development which has negative effects on the environment such as changes in the natural flow of rivers, disruption of the population of aquatic biota that live in these watersheds and has the risk of potential disasters if the dam fails. In fact, the energy potential from the mini-micro hydro source is 19,835 MW, but its utilization is still very low around 100 MW. Therefore, the extraction of water flow energy in the form of rivers and irrigation channels with very low head altitude differences is considered important and urgent so that a gravity vortex turbine-based mini / micro hydro research is proposed. Specifically, this study aims to analyze the performance of the vortex turbine with backward and forward blades in a conical basin through laboratory experimental devices. Experiments were carried out on a fluid flow rate of 120 liters per minute (lpm) and 100 lpm by loading using a prony brake dynamometer in order to obtain torque performance data on variations in turbine blade rotational speed. In this experiment, the results showed that the performance of the backward blade turbine was superior with its optimal efficiency reaching 36.7% at a discharge of 120 lpm and a rotating speed of 80 rpm than the forward blade which at a discharge of 120 lpm and a rotating speed of 80 rpm was only able to achieve its highest efficiency at 33.19%.